Chiral Dielectric Metasurfaces: Optomechanics of Chiral Dielectric Metasurfaces (Advanced Optical Materials 4/2020). Issue 4 (19th February 2020) - Zanotto, Simone; Tredicucci, Alessandro; Navarro‐Urrios, Daniel; Cecchini, Marco; Biasiol, Giorgio; Mencarelli, Davide; Pierantoni, Luca; Pitanti, Alessandro
Abstract : This cover picture, referring to article number 1901507 by Simone Zanotto and co‐workers, illustrates a mechanically compliant and optically resonant membrane, patterned with engineered L‐shaped holes, which allows to handle light polarization – and light chirality – as shown by the colored paths on the superimposed Poincaré sphere. Given the ubiquity of polarized light in applied sciences, the studied device may prove useful in several fields such as biophotonics, material science, drug discovery, and telecommunications.